Effects of Water/CO2 on the Shear Mechanical Properties of Straight Jointed Sandstone - LI Guobin; SHEN Yongxing; FENG Zengchao (Taiyuan Ligong Daxue xuebao)
[Purposes] The injection of water and/or CO2 alters the shear characteristics of jointed rock, directly impacting the stability of the sequestered formation. Thus, the influence of water injection and CO2 injection on the shear characteristics of jointed rock mass is explored. [Methods] Shear tests were carried out on flat jointed sandstone under three test conditions: drying, water injection, and CO2 injection. The changes of shear strength with confining pressure, injected fluid type, and injection fluid pressure were investigated. [Findings] The results indicate the following: The shear stress-shear displacement curves for straight jointed sandstone under all three test conditions (dry, CO2 injection, and water injection) exhibit a sliding failure pattern; Water/CO2 injection will weaken the shear strength of straight jointed rock, and the weakening effect of water is stronger than that of CO2; The empirical formula between shear strength and confining pressure, injection fluid type, and fluid injection pressure is proposed. The average error between experimental and theoretical data is 5.69%. [Conclusions] This research work is of great significance for predicting the shear strength of sandstone after water/CO2 injection, optimizing the construction scheme, and improving the construction safety.